2015
DOI: 10.1186/s12913-015-0829-9
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective, matched cohort study of potential drug-drug interaction prevalence and opioid utilization in a diabetic peripheral neuropathy population initiated on pregabalin or duloxetine

Abstract: BackgroundAnticipating and controlling drug-drug interactions (DDIs) in older patients with painful diabetic peripheral neuropaty (pDPN) presents a significant challenge to providers. The purpose of this study was to examine the impact of newly initiated pregabalin or duloxetine treatment on Medicare Advantage Prescription Drug (MAPD) plan pDPN patients’ encounters with potential drug-drug interactions, the healthcare cost and utilization consequences of those interactions, and opioid utilization.MethodsStudy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…In two recently published articles evaluating, among others, the drug interactions of duloxetine and pregabalin in the treatment of fibromyalgia and diabetic neuropathy [41,42], the authors considered a major interaction of pregabalin to be the reduction of the drug's efficacy by naproxen or ketorolac that they found in the Micromedex 2.0 database. This interaction, however, is not reported in the information brochure of the drug [40], nor can it be found as a publication.…”
Section: Pharmacodynamic Interactionsmentioning
confidence: 98%
“…In two recently published articles evaluating, among others, the drug interactions of duloxetine and pregabalin in the treatment of fibromyalgia and diabetic neuropathy [41,42], the authors considered a major interaction of pregabalin to be the reduction of the drug's efficacy by naproxen or ketorolac that they found in the Micromedex 2.0 database. This interaction, however, is not reported in the information brochure of the drug [40], nor can it be found as a publication.…”
Section: Pharmacodynamic Interactionsmentioning
confidence: 98%
“…Reasons include shortfalls in proper patient and pain assessment, insufficient diagnostic accuracy, and inadequate knowledge about medications and their appropriate clinical use, combined with relatively limited treatment efficacy [ 5 ]. Patient, clinician, and health care system factors interact to affect these outcomes in pain [ 6 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with neuropathic pain are commonly treated with a wide range of drugs to improve symptoms and comorbidities, including pain, sleep dysfunction, and anxiety . Studies have shown that DDIs can significantly increase health care utilization and costs . Therefore, it is critical to characterize any potential DDIs that may negatively impact optimal clinical management.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Studies have shown that DDIs can significantly increase health care utilization and costs. 34,35 Therefore, it is critical to characterize any potential DDIs that may negatively impact optimal clinical management.…”
Section: Discussionmentioning
confidence: 99%